2017
DOI: 10.1038/hr.2016.190
|View full text |Cite
|
Sign up to set email alerts
|

The effects of missed doses of amlodipine and losartan on blood pressure in older hypertensive patients

Abstract: This randomized, double-blind, parallel-group, multicenter study compared the efficacy of amlodipine and losartan in an older hypertensive population, focusing on therapeutic coverage in the case of missed doses. Following a 4-week, single-blind, placebo washout period, 211 patients were randomly assigned to receive either 5 mg of amlodipine once daily or 50 mg of losartan once daily. Doses were doubled after 6 weeks of treatment if the diastolic blood pressure exceeded 90 mm Hg. After the 12-week treatment pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Similarly, participants without falls due to physical discomfort in the last 6 months were more likely to have good medication adherence than those with falls. This finding was consistent with that reported by Berry et al (Berry et al., 2010 ), which showed an increased risk of falls in people with poor medication adherence, possibly because the risk of falls increased with a gradual rise in blood pressure resulting from poor medication adherence (de Leeuw et al., 2017 ). Few studies have indicated a higher risk of falls at the start of pharmacotherapy (Butt et al., 2012 , 2013 ; Shimbo et al., 2016 ).…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, participants without falls due to physical discomfort in the last 6 months were more likely to have good medication adherence than those with falls. This finding was consistent with that reported by Berry et al (Berry et al., 2010 ), which showed an increased risk of falls in people with poor medication adherence, possibly because the risk of falls increased with a gradual rise in blood pressure resulting from poor medication adherence (de Leeuw et al., 2017 ). Few studies have indicated a higher risk of falls at the start of pharmacotherapy (Butt et al., 2012 , 2013 ; Shimbo et al., 2016 ).…”
Section: Discussionsupporting
confidence: 92%
“…A number of observational studies have consistently identified a higher risk of falling following antihypertensive medication initiation or titration 7–12. Patients with poor medication adherence, specifically poor implementation of antihypertensive pharmacotherapy, characterised by gaps in antihypertensive medication use, may experience a gradual rise in blood pressure 27–29. On resumption of therapy, similar to initial use, patients may be at a greater risk for falls relative to those who do not have gaps in antihypertensive therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Participants’ blood pressure during the follow-up period was not measured to assess fluctuations in blood pressure. However, the ability of antihypertensive drugs to lower blood pressure have been proven in clinical trials,1–3 and clinical studies have shown that withdrawal of these medications leads to a gradual rebound in blood pressure 27–29. Furthermore, the feasibility of undertaking these measurements, which would likely require daily measurements, is unlikely in large observational studies such as this.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations